Geoinformation analysis of the influence of repair and construction works on the investment attractiveness of real estate - Pomortseva, Оlena; Pankiv, Volodymyr; Kobzan, Sergiy (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Міжнародні відносини, економіка, країнознавство, туризм, 2024)
The article considers the actual problem of investing in the primary real estate market. The subject of the research is the residential real estate market in different regions of Ukraine. The purpose of the article is to research residential real estate on the primary market of Ukraine, depending on its condition. The type of repair has a significant impact on the final cost of an apartment in a new building. The ratio of the cost of an apartment without repairs and the cost of further repairs, as well as the region where the apartment is located, can provide an answer to the expediency of investing funds by the stakeholder. Such a large number of factors cannot be taken into account without the use of geographic information systems, which enable both the accumulation and processing of large data sets and the use of spatial reference. The purpose of the article is to study the changes in the cost of renting and selling m2 of the primary market of residential real estate depending on the city of Ukraine and the impact of different types of repairs on the real estate value. As well as determination of the capitalization rate by regions that were studied. During the research, general scientific methods of system analysis and geostatistics methods were used to transform data from a discrete to a continuous form of representation when processing arrays of data on various types of real estate. The work uses the direct capitalization method to determine the rate of return. During the research, cartograms were constructed for different cities of Ukraine regarding the average cost and rental rate per m2 of real estate in the primary market. The influence of various types of repairs on the value of real estate was studied. The capitalization rate was determined for the regions studied. Conclusions were drawn regarding the prospects for investing in the residential real estate market, as well as options for investing in real estate in different cities of Ukraine and obtaining maximum returns. The results obtained by the authors will be useful to stakeholders, realtors, appraisers and other market specialists for calculating returns on the primary real estate market.